2011
DOI: 10.1007/s12035-011-8189-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Myelin Basic Protein Gene Expression by Acetyl-l-Carnitine

Abstract: Acetyl-L-carnitine (ALC), the acetyl ester of L-carnitine, is a naturally occurring molecule which plays an essential role in intermediary and mitochondrial metabolism. It has also neurotrophic and antioxidant actions, demonstrating efficacy and high tolerability in the treatment of neuropathies of various etiologies. ALC is a molecule of considerable interest for its clinical application in various neural disorders, although little is known regarding its effects on gene expression. Suppression subtractive hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
2
14
0
1
Order By: Relevance
“…Besides the afore mentioned role on mitochondrial bioenergetics, which allows brain cells to restore altered redox balance (Calabrese et al, 2010c(Calabrese et al, , 2009a, ALC is neuroprotective through a variety of other effects such as the increase in PKC activity and modulation of synaptic plasticity via NMDA receptor expression and increase in the production of neurotrophins (Vivoli et al, 2010). Importantly, treatment with ALC induces up-regulation of the gene coding for Hsp72 explaining its protective effects in inflammation, neurodegenerative disorders, and aging (Calabrese et al, 2004b;Traina et al, 2011). Defects in the function of complexes II and III have been observed in Huntington's disease patients (Jones et al, 2010), while complex IV is involved in the mitochondrial dysfunction underlying the pathogenesis of AD.…”
Section: The Carnitine Systemmentioning
confidence: 99%
“…Besides the afore mentioned role on mitochondrial bioenergetics, which allows brain cells to restore altered redox balance (Calabrese et al, 2010c(Calabrese et al, , 2009a, ALC is neuroprotective through a variety of other effects such as the increase in PKC activity and modulation of synaptic plasticity via NMDA receptor expression and increase in the production of neurotrophins (Vivoli et al, 2010). Importantly, treatment with ALC induces up-regulation of the gene coding for Hsp72 explaining its protective effects in inflammation, neurodegenerative disorders, and aging (Calabrese et al, 2004b;Traina et al, 2011). Defects in the function of complexes II and III have been observed in Huntington's disease patients (Jones et al, 2010), while complex IV is involved in the mitochondrial dysfunction underlying the pathogenesis of AD.…”
Section: The Carnitine Systemmentioning
confidence: 99%
“…Several studies carried out in vertebrate models and humans illustrate the effects of ALC in the nervous system including its effect in improving the cognitive capability likely due to its protective actions against several physiological and pathological brain modifications induced by aging (Calabrese et al, 2012;Tolu et al, 2002), diseases (Shea, 2007;Torrioli et al, 2008;Traina et al, 2006Traina et al, , 2008aTraina et al, , 2008bTraina et al, , 2009Traina et al, , 2011 and drug abuse (Coccurello et al, 2007;Scheggi et al, 2004) rather than to its actual action on the mechanisms underlying learning processes. Recently, a role of ALC in the modulation of pain perception has been demonstrated mostly in the treatment of neuropathies of various origins (Chiechio et al, 2010;Sima, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[5] A deficiency of acetyl-L-carnitine (ALC) and L-carnitine (LC) seems to play a pivotal role in this pathway [6], since a deficit of ALC has been shown to cause damage to the myelin sheath. [7] In animal models, the exogenous administration of ALC increases artemin levels and enhances the expression of nerve growth factor (NGF) [8,9], enhances antioxidant activity [10] and microvascular protein permeability [11], and induces long-term upregulation of the presynaptic mGlu2 receptors [12]; in this way, ALC supplementation induces neuroprotective, neurotrophic and analgesic effects in the peripheral nervous system. [12,13] Regarding human beings, ALC is recommended in the tier 1 of neuropathic pain treatments by the Mayo Clinic proceedings [14], and a recent meta-analysis has confirmed that administration of ALC was able to improve pain perception in people affected by peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%